When myocardial infarction is not only inferior: the importance of prehospital recognition of right ventricular infarction - Ilić, Andrijana; Vukićević, Verica; Mirković, Olja; Zmijarević, Vanja; Stefanović, Ivana; Aćimović, Bojana; Ristić Mrkalj, Radmila (Halo 194 Scientific Journal of Emergency Medicine, 2026)
Introduction: Right ventricular myocardial infarction (RVI) occurs with complete occlusion of the right coronary artery proximal to the site of separation of the branches feeding the right ventricular wall. It rarely occurs independently, but it complicates about 50% of inferior infarctions. Clinically, it is recognized by the triad: hypotension, jugular venous distension and "clean" lungs. Vasodilators are contraindicated, while intravenous fluid replacement is the key of mennagement. Case report: A 50-year-old man complains of sudden shoulder pain, nausea and sweating. The ECG shows an infarction of inferior localization, with the greatest ST elevation in lead D3, combined with the clinical triad of RV infarction. ST elevation was also confirmed in V4R-V6R (Erhardt's sign). A rapid infusion of cristalloids was administrated, which led to an improvement in hemodynamics. Conclusion: Due to the worse prognosis of patients with right ventricular myocardial infarction and possible iatrogenic complications, early recognition and adequate treatment.
Keywords: Right ventricular infarction; hypotension; Erhardt's sign; RVI